Public open space characteristics influencing adolescents' use and physical activity: A systematic literature review of qualitative and quantitative studies. (May 2018) - Van Hecke, Linde; Ghekiere, Ariane; Veitch, Jenny; Van Dyck, Delfien; Van Cauwenberg, Jelle; Clarys, Peter; Deforche, Benedicte
Abstract: The objective of this systematic review was to provide insight into the specific characteristics of public open spaces (POS) associated with adolescents' POS visitation and physical activity (PA). Qualitative research suggests many characteristics to be associated with POS visitation and PA. Quantitative evidence confirmed a positive association between presence of trails, playgrounds and specific types of sports fields (e.g. basketball) with POS visitation and PA, whereas safety and aesthetics seemed subordinate. Suggestions for future research, as well as some methodological recommendations are provided. Highlights: POS can be an important place to accumulate PA among adolescents. Adolescents perceive that many public open spaces are designed for younger children. Presence of playgrounds and trails within POS may stimulate POS visitation and PA. Experimental and other well-designed research studies are warranted.